PRAGMALINGUISTIC ASPECTS OF IRONY - Parmonov Alisher (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The purpose of this article is to discuss and find out some features of pragmalinguistics in linguistics. Moreover, it illustrates a stylistic device as well as a literal device that is called “irony” and usage of irony in poems written by A. Oripov, an uzbek poet.